Preparation and thermal properties of cellulose acetate/polystyrene blend nanofibers via electrospinning technique - Rosdi, Nurul Husna; Mohd Kanafi, Nafeesa; Abdul Rahman, Norizah (Universiti Putra Malaysia Press, 2018)
Cellulose acetate (CA) is an interesting material due to its wide spectrum of utilities across different domains ranging from absorbent to membrane filters. In this study, polystyrene (PS) nanofibres, and cellulose acetate/polystyrene (CA/PS) blend nanofibres with various ratios of CA: PS from 20: 80 to 80: 20 were fabricated by using electrospinning technique. The SEM images show that the nanofibres exhibited non-uniform and random orientation with the average fibre diameter in the range of 100 to 800 nm. It was found that the incorporation of PS had a great effect on the morphology of nanofibre. At high proportion of PS, no or less beaded CA/PS nanofibres were formed. Thermal properties of the composite nanofibres were investigated by using thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) techniques. The TGA results showed thermal stability of CA/PS nanofibres were higher than pristine CA.